Age-Related Differences in Corticospinal Excitability and Anticipatory Postural Adjustments of the Trunk - Rowland, Rebecca S.; Jenkinson, Ned; Chiou, Shin-Yi (Frontiers in Aging Neuroscience, 2021)
Anticipatory postural adjustments (APAs) are a feedforward mechanism for the maintenance of postural stability and are delayed in old adults. We previously showed in young adults that APAs of the trunk induced by a fast shoulder movement was mediated, at least in part, by a cortical mechanism. However, it remains unclear the relationship between delayed APAs and motor cortical excitability in ageing. Using transcranial magnetic stimulation we examined motor evoked potentials (MEPs) of the erector spinae (ES) muscles in healthy young and old adults prior to a fast shoulder flexion task. A recognition reaction time (RRT) paradigm was used where participants responded to a visual stimulus by flexing their shoulders bilaterally as fast as possible. Activity of bilateral anterior deltoid (AD) and ES muscles were recorded using electromyography (EMG). Onset of AD and ES EMG was measured to represent RRT and APAs, respectively. We found increases in amplitudes of ES MEPs at 40ms than 50ms prior to the EMG onset of the AD in both groups. The amplitude of ES MEPs at 40ms prior to the onset of AD EMG correlated with the onset of ES activity counterbalancing the perturbation induced by the shoulder task in the elderly participants only. Our findings suggest that timing of increasing corticospinal excitability prior to a self-paced perturbation becomes more relevant with ageing in modulating postural control of the trunk.